Sejarah Dan Transformasi Arbitrase Dalam Menakar Relevansi Penyelesaian Sengketa Alternatif Di Zaman Kontemporer - Muhammad Ramadhani (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This paper examines the historical development of arbitration and Alternative Dispute Resolution (ADSR) mechanisms in Indonesia, their normative and institutional transformations, and their relevance to addressing dispute resolution needs in the contemporary era. The research employs a juridical-normative method with a library research approach, focusing on the analysis of legal norms, legal principles, and doctrines related to arbitration and ADSR. The research data sources consist of primary legal materials in the form of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court, and various relevant court decisions. Secondary legal materials are obtained from books, scientific journal articles, research findings, and policy documents accessed through various library sources and digital media. This research also uses a historical approach to trace the development of arbitration from the colonial period to the modern era, and a conceptual approach to analyze the effectiveness, urgency, and relevance of ADSR in the current Indonesian legal system. The study shows that arbitration and the APS have undergone a significant transformation. While in its early stages of development, arbitration was viewed as an alternative mechanism with limited use in certain trade disputes, it has now evolved into a crucial instrument in the modern dispute resolution system. This transformation is marked by strengthened regulations, the development of national arbitration institutions, increased recognition of arbitral awards, and the increasingly widespread use of APS in various legal and business fields. Amidst the increasing number of cases filed with the courts, the complexity of legal relations, and the development of the digital economy and globalization, APS offers a dispute resolution mechanism that is faster, more flexible, more efficient, and more oriented towards the needs of the parties. Abstrak Tulisan ini mengkaji perkembangan sejarah arbitrase dan mekanisme Alternatif Penyelesaian Sengketa (APS) di Indonesia, transformasi normatif dan kelembagaannya, serta relevansinya dalam menjawab kebutuhan penyelesaian sengketa pada era kontemporer. Penelitian menggunakan metode yuridis-normatif dengan pendekatan kepustakaan (library research), yang berfokus pada analisis norma hukum, asas hukum, dan doktrin yang berkaitan dengan arbitrase serta APS. Sumber data penelitian terdiri atas bahan hukum primer berupa Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa, Peraturan Mahkamah Agung Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan, serta berbagai putusan pengadilan yang relevan. Adapun bahan hukum sekunder diperoleh dari buku, artikel jurnal ilmiah, hasil penelitian, dan dokumen kebijakan yang diakses melalui berbagai sumber kepustakaan maupun media digital. Penelitian ini juga menggunakan pendekatan historis untuk menelusuri perkembangan arbitrase sejak masa kolonial hingga era modern, serta pendekatan konseptual untuk menganalisis efektivitas, urgensi, dan relevansi APS dalam sistem hukum Indonesia saat ini. Hasil kajian menunjukkan bahwa arbitrase dan APS telah mengalami transformasi yang sangat signifikan. Jika pada masa awal perkembangannya arbitrase hanya dipandang sebagai mekanisme alternatif yang digunakan secara terbatas dalam sengketa perdagangan tertentu, kini arbitrase telah berkembang menjadi instrumen penting dalam sistem penyelesaian sengketa modern. Transformasi tersebut ditandai dengan penguatan regulasi, berkembangnya lembaga arbitrase nasional, meningkatnya pengakuan terhadap putusan arbitrase, serta semakin luasnya penggunaan APS dalam berbagai bidang hukum dan bisnis. Di tengah meningkatnya jumlah perkara yang masuk ke pengadilan, kompleksitas hubungan hukum, serta perkembangan ekonomi digital dan globalisasi, APS menawarkan mekanisme penyelesaian sengketa yang lebih cepat, fleksibel, efisien, dan berorientasi pada kebutuhan para pihak.